Aerosol measurements during OASIS Barrow field intensive Spring 2009 - Jim Smith; Steve Sjostedt; Jonathan Abbatt; Alfred Wiedensohler (Arctic Data Center)
The NCAR "Particle Size Distribution" (PSD) instrument consists of three instruments that measure the size distribution of the ambient aerosol from 3 nm to 2 microns. General specifications for the instrument during Ocean-Atmosphere-Sea Ice-Snowpack (OASIS) are as follows: * Size range: ~3.85 nm to 2 micron * Number of diameter bins: 75 * Time resolution: 5 min Please see included documentation for full details.